Study on Morphological Characteristics of Different Genotypes of Gladiolus Flower (Journal of Science Foundation, 2013)
The experiment was carried out during the period from November2008 to October, 2009 to compare the morphology of five gladiolus flowers genotypes with respect to plant height, length and breadth of leaf, number of leaves per plant, length of flowers, breadth of flower, weight of flower, weight of single stick, length of spike, length of rachis, flowers per plant, days to reach 50% spike initiation, number of corm and cormel per plant, breadth of corm and weight of cormel per plant. The results indicated the significant variation amongst the gladiolus genotypes with respect to studied morphological characteristics as well as with yield, yield attributes and plant height. The plant height was higher (58.6cm) and lower (46.52cm) in yellow and orange /red respectively due to genotype. The lengths of leaves were almost same but higher with yellow and violet (42.25/42.05 cm) than the white and orange ones where the smallest length was recorded for red (33.36cm) one. Almost same trends were recorded for breadth of leaves with the exception of few. The average number of leaves was highest for white (12.25) followed by red, violet, orange and yellow respectively. Most of the parameters of flower characteristics did not maintain regular trend and correlation when considered in terms of sequences starting from white to red as shown in the table 1, 2 and 3. The recorded results clearly indicate that the white genotype has the best planting materials which may be planted for luxuriant growth of plants and production of excellent flowers. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14642 J. Sci. Foundation, 9(1&2): 1-8, June-December 2011